1999
DOI: 10.1007/s004030050418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12- O -tetradecanoyl-phorbol ester and incisional wounding on neuropsin mRNA and its protein expression in murine skin

Abstract: The expression of neuropsin mRNA in vivo in mouse skin was examined by in situ hybridization and Northern blotting under stimulated conditions. Two kinds of epidermal stimuli, a topical application of a chemical tumor promoter and incisional wounding, were used. A single topical application of 12-O-tetradecanoyl-phorbol 13-acetate induced epidermal hyperplasia and simultaneously induced an extensive increase in neuropsin mRNA in the suprabasal cells. A full-thickness skin incision also induced a profound incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 23 publications
4
18
0
Order By: Relevance
“…Like other kallikreins, KLK8 exhibits a broad expression profile in many tissues. However, KLK8 is most prominently expressed in the brain, the mucosa, and the skin, where it has roles in tissue homeostasis, desquamation of cells, ECM remodelling, and wound healing (67,72,73). Since it has been speculated that HPV particles may be structurally primed for entry already at the site of assembly in the upper layers of the epithelium (25), authentic HPV might be cleaved by KLK8 at the site of desquamation prior to transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Like other kallikreins, KLK8 exhibits a broad expression profile in many tissues. However, KLK8 is most prominently expressed in the brain, the mucosa, and the skin, where it has roles in tissue homeostasis, desquamation of cells, ECM remodelling, and wound healing (67,72,73). Since it has been speculated that HPV particles may be structurally primed for entry already at the site of assembly in the upper layers of the epithelium (25), authentic HPV might be cleaved by KLK8 at the site of desquamation prior to transmission.…”
Section: Discussionmentioning
confidence: 99%
“…This was particularly evident for the sizeable group of extracellular matrix-degrading proteases and their receptors and inhibitors, whose expression is known to be strongly upregulated (although stoichiometrically still being present in minute amounts) in migrating keratinocytes at the wound edge. These included the urokinase plasminogen activator, urokinase plasminogen activator receptor, plasminogen activator inhibitor-1, matriptase/MT-SP1, neuropsin, and matrix metalloproteinases 3, 9, 10, and 13 (Romer et al, 1996;Madlener et al, 1998;Kitayoshi et al, 1999;Lund et al, 1999, unpublished data). The improvement of methods for RNA isolation, reverse transcription, and hybridization, and the use of more sensitive arrays should overcome such limitations in sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that Klk8 mRNA was induced by an external stimulus, such as the application of 12-O-tetradecanoylphorbol-13-acetate (TPA), which causes epidermal proliferation and hyperkeratosis like psoriasis of human skin (15). In the present study, we used TPA to compare the reaction of WT and Klk8 Ϫ/Ϫ mouse skin.…”
mentioning
confidence: 95%